Super-mini percutaneous nephrolithotomy (SMP) vs retrograde intrarenal surgery (RIRS) in the management of renal calculi <= 2 cm: A propensity matched study - Pillai, Sunil Bhaskara; Chawla, Arun; de la Rosette, Jean J. M. C. H.; del Pilar Laguna Pes, Maria; Guddeti, Rajsekhar; Reddy, Suraj Jayadeva; Sabnis, Ravindra; Ganpule, Arvind; Desai, Mahesh; Parikh, Aditya (Springer, 2022)
Objective: To compare the effectiveness and safety of Super-Mini PCNL (SMP) and Retrograde Intrarenal Surgery (RIRS) in the management of renal calculi ? 2 cm. Patients and methods: A prospective, inter-institutional, observational study of patients presenting with renal calculi ? 2 cm. Patients underwent either SMP (Group 1) or RIRS (Group 2) and were performed by 2 experienced high-volume surgeons. Results: Between September 2018 and April 2019, 593 patients underwent PCNL and 239 patients had RIRS in two tertiary centers. Among them, 149 patients were included for the final analysis after propensity-score matching out of which 75 patients underwent SMP in one center and 74 patients underwent RIRS in the other. The stone-free rate (SFR) was statistically significantly higher in Group 1 on POD-1 (98.66% vs. 89.19%; p = 0.015), and was still higher in Group 1 on POD-30 (98.66% vs. 93.24%, p = 0.092) SFR on both POD-1 and POD-30 for lower pole calculi was higher in Group 1 (100 vs. 82.61%, p = 0.047 and 100 vs 92.61% p = 0.171). The mean (SD) operative time was significantly shorter in Group 1 at 36.43 min (14.07) vs 51.15 (17.95) mins (p < 0.0001). The mean hemoglobin drop was significantly less in Group 1 (0.31 vs 0.53 gm%; p = 0.020). There were more Clavien–Dindo complications in Group 2 (p = 0.021). The mean VAS pain score was significantly less in Group 2 at 6 and 12 h postoperatively (2.52 vs 3.67, 1.85 vs 2.40, respectively: p < 0.0001), whereas the mean VAS pain score was significantly less in Group 1 at 24 h postoperatively (0.31 vs 1.01, p < 0.0001). The mean hospital stay was significantly shorter in Group 1 (28.37 vs 45.70 h; p < 0.0001). Conclusion: SMP has significantly lower operative times, complication rates, shorter hospital stay, with higher stone-free rates compared to RIRS. SMP is associated with more early post-operative pain though.
Keywords: Flexible; Miniaturization; PCNL; Renal Stones; RIRS; SMP